CSR reporting in China's private and state-owned enterprises: A mixed methods comparative analysis - Irina Ervits (Asian Business & Management, 2021)
The paper pursues a mixed methods approach of conducting both quantitative and qualitative content analysis of corporate social responsibility (CSR) reports in two types of Chinese companies: State-owned (SOE) and non-state-owned (non-SOE) enterprises. Quantitative content analysis revealed overall homogeneity in CSR reporting among SOEs and non-SOEs in China, which can be explained by coercive isomorphism on a national scale. The Chinese government has created an intricate system of incentives encouraging both SOEs and non-SOEs to engage in socially responsive behavior and disclosure. As a result of qualitative analysis, a recurring theme of "strategic emerging industries" (SEI) was identified in the CSR reports of predominantly state-owned banks. This finding provides empirical evidence of the link between the social and economic objectives of the Chinese government, and it shows how state-owned banks mediate between the state and business (SOEs and non-SOEs) as part of a coercive isomorphism apparatus.
Keywords: 650; CSR reporting; Soes; State-owned enterprises; Strategic emerging industries; China